Procesos académicos por criterios de aseguramiento de la calidad de la carrera de Enfermería de la Universidad Estatal de Bolívar periodo octubre 2018 abril 2019 - Espin Chico, Marcia Jimena (2019)
The theme ACADEMIC PROCESSES FOR THE QUALITY ASSURANCE CRITERIA OF THE NURSING CAREER OF THE STATE UNIVERSITY OF BOLÍVAR PERIOD OCTOBER 2018 APRIL 2019 was developed with the motive of development to improve the execution of the academic processes of the Nursing Career in quality matter. Under this framework, this research work responds to the need to deepen and promote the standardized knowledge of the Academic Processes of Student Tutorials, Linking with Society, Experimental Practical Learning and Preprofessional Practices in the Faculty of Health Sciences and Human Being of Bolívar State University, specifically in the Nursing Degree. The main objective defined to address research was the determination of academic processes by quality assurance criteria as established by CACES. This objective is known through the application of quantitative tools the current situation of the applied knowledge around each process by both the student population and the teachers of the Race, determined that despite having the basic notions, it is necessarily difficult in a way unified with the Process Manual defined in this investigation the activities of each indicator. In the same order of ideas, the descriptive techniques in this research allowed to define and structure the matrices of activities and flowcharts that make up the Manual of Academic Processes by Criteria of the Quality of the Nursing Career proposed by this research. Keywords: Academic Processes, Quality, Nursing, Tutoring, Linking, Pre-professional Practices, Experimental Practical Learning